Popular songs and national identity in Malawi - Nurse, George T. (International Library of African Music, 1964)
The present paper is a modest attempt to fill in one of the blank spots on our ethno- musicological map of East Africa. It cannot be more than a preliminary superficial account of music and musical instruments in the wide territory of Northern Mozambique. Further research trips will have to be done in the coming years in order to check all the information that was given to me, and to collect more material, so that we may gain a more extensive knowledge of the area. Many problems and questions have been raised in this paper. They can only be solved through intensive analytical and comparative studies of the present and additional material. The author would be glad, in this context, if he could be informed of any other recordings of music from Northern Mozambique that have been made or are being made. There remains still much of the collected material to study. In particular, an analysis of the 8 mm film strips, together with a detailed analysis of all the tape recordings, will give us plenty of further insight.
Keywords: Folk dancing; National songs; Musical instruments; Mbira; Ethnomusicology; Patriotic music; Mbira music; Zambia; Malawi; Mozambique; African Music; Mbira (Instrument)